1989
DOI: 10.1177/070674378903400717
|View full text |Cite
|
Sign up to set email alerts
|

Trichotillomania in a Ten Year Old Boy: Gender Identity Issues Formulated in Terms of Individual and Family Factors*

Abstract: The case study of a ten year old boy who presented with trichotillomania and symptoms of gender identity confusion is described and formulated in terms of the individual and family factors involved. This approach is presented as more tangible and useful than the traditional method using psychoanalytic theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Fatores pessoais inespecíficos, como início da menarca 16 , fase do ciclo menstrual 17,18 , doença clínica, dificuldades acadêmicas ou tensões na escola [19][20][21] , divórcio dos pais 21 , morte, doença ou dano familiar, nascimento ou rivalidade com um irmão 19,20,22,23 , mudança de residência 24,25 , separação de amigos 26 , breve separação dos pais 27 , imobilidade forçada 28 , castigo por ter que cortar o cabelo ou ter que cortar "careca" por ordem dos pais 29 , parecem se relacionar com os sintomas da TTM.…”
Section: Classificação E Diagnósticounclassified
“…Fatores pessoais inespecíficos, como início da menarca 16 , fase do ciclo menstrual 17,18 , doença clínica, dificuldades acadêmicas ou tensões na escola [19][20][21] , divórcio dos pais 21 , morte, doença ou dano familiar, nascimento ou rivalidade com um irmão 19,20,22,23 , mudança de residência 24,25 , separação de amigos 26 , breve separação dos pais 27 , imobilidade forçada 28 , castigo por ter que cortar o cabelo ou ter que cortar "careca" por ordem dos pais 29 , parecem se relacionar com os sintomas da TTM.…”
Section: Classificação E Diagnósticounclassified
“…In general, Elder and Caspi (1990) found that adolescent girls are at significant psychological risk when living in families under stress, such as marital conflict, economic hardship, or loss of a parent. More directly, studies have shown that the onset of TTM can be associated with changes in residence (Muller & Winkelmann, 1972), separation from friends (Schnurr, 1988), problems in school (Oranje, Peereboom-Wynia, & De Raeymaecker, 1986), separation from parents (Schnurr & Davidson, 1989), and sibling rivalry (Oranje et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Monroe & Abse (1963) o ato de comer a raiz ou o cabelo (tricofagia) faria parte do ritual do pacientes com TTM e sugeriria um significado fálico. Ansiedade e confusão sobre função sexual ou gravidez são temas recorrentes entre outros autores (Aleksandrowicz & Mares, 1978;Buxbaum, 1960;Ilan & Alexander, 1965;Schnurr & Davidson, 1989;Sperling, 1968).…”
Section: Abordagem Psicodinâmicaunclassified